Proposal of a methodology for pre-selection of sewage treatment systems within watersheds - Fantin,Lucas Luiz Dall'Orto (2017)
ABSTRACT The selection of sewage treatment plants within watersheds is a complex process when there are multiple outflows presenting different loads and watercourses presenting different assimilation capabilities. In this context, the present study aims to establish a methodology for pre-selection of wastewater treatment alternatives within watersheds. The methodology involves the combined use of water quality model, optimization technique and a set of technical and economic criteria associated with different wastewater treatment systems. To evaluate the proposed methodology there were considered different effluent disposal scenarios in the Pardo river watershed. Pardo is a major tributary of the Itapemirim river, watercourse located in the southern portion of Espírito Santo State, Brazil. The results indicated that the optimization model, that aimed to minimize wastewater treatment efficiencies within the watershed, considering watercourses self-purification capacities, selected treatment systems ranging from the combination of UASB and polishing lagoons systems to slow infiltration, treatment alternatives that presented the lowest net cost estimates. The incorporation of equity perspective between treatment systems increased the total present net cost associated with wastewater treatment within the watershed.